KETERAMPILAN LITERASI INFORMASI MAHASISWA DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Majidah Majidah; Dian Hasfera; M Fadli (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
The scope of higher education in the era of Industry Revolution 4.0 (IR 4.0) is one of the complex, dialectical studies and becomes an opportunity that has the potential to change society for the better. IR 4.0 is accommodated by artificial intelligence in the form of technology that will change the work environment from tasks with conventional characteristics to digital technology-based. This condition requires far more numerous teaching, research and interdisciplinary innovations. One of the skills that is an important concern in the realm of higher education in the IR 4.0 era is the information literacy skills that must be possessed by students. Information skills are concentrated on cognitive and transferable skills, such as problem solving, evaluation and communication skills. Information Literacy (IL) deals with the ability to access, evaluate, organize and use information to study, solve problems, make decisions in the context of formal and informal learning, at work, at home and in the educational environment. The purpose of this paper is to discuss what happened to the education system in the era of IR 4.0 and the skills that must be possessed by students in dealing with education in the era of IR 4.0.